1996
DOI: 10.1128/jb.178.12.3531-3538.1996
|View full text |Cite
|
Sign up to set email alerts
|

Splicing of a group II intron involved in the conjugative transfer of pRS01 in lactococci

Abstract: Analysis of a region involved in the conjugative transfer of the lactococcal conjugative element pRS01 has revealed a bacterial group II intron. Splicing of this lactococcal intron (designated Ll.ltrB) in vivo resulted in the ligation of two exon messages (ltrBE1 and ltrBE2) which encoded a putative conjugative relaxase essential for the transfer of pRS01. Like many group II introns, the Ll.ltrB intron possessed an open reading frame (ltrA) with homology to reverse transcriptases. Remarkably, sequence analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
192
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(195 citation statements)
references
References 47 publications
(55 reference statements)
2
192
1
Order By: Relevance
“…The maturase activity of LtrA promotes intron splicing by stabilizing the catalytically active tertiary conformation of the ribozyme (Matsuura et al 1997). Ll.LtrB was found on two highly similar conjugative elements of L. lactis: a conjugative plasmid, pRS01 (Mills et al 1996), and a chromosomal sex factor (Shearman et al 1996). In both elements, Ll.LtrB interrupts the ltrB gene coding for relaxase (LtrB) at the same position.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maturase activity of LtrA promotes intron splicing by stabilizing the catalytically active tertiary conformation of the ribozyme (Matsuura et al 1997). Ll.LtrB was found on two highly similar conjugative elements of L. lactis: a conjugative plasmid, pRS01 (Mills et al 1996), and a chromosomal sex factor (Shearman et al 1996). In both elements, Ll.LtrB interrupts the ltrB gene coding for relaxase (LtrB) at the same position.…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme is thus essential for conjugation, and splicing of Ll.LtrB from its pre-mRNA transcript is necessary for LtrB production and subsequent DNA transfer. Therefore, Ll.LtrB splicing controls conjugation efficiency of its host elements (Mills et al 1996;Shearman et al 1996). We previously developed a sensitive splicing/conjugation assay in L. lactis to show that Ll.LtrB trans-splices when fragmented at natural group II intron fragmentation sites.…”
Section: Introductionmentioning
confidence: 99%
“…1), predicted to encode a relaxase protein, is most closely related (at both the DNA and protein sequence levels) to the ItrB gene of the lactococcal conjugative element pRS01 (Mills et al, 1994). An interesting feature of ltrB is that the wild-type allele is interrupted by the self-splicing, mobile group II intron Ll.ltrB, the first fully functional group II intron identified in bacteria (Mills et al, 1996). We recently showed that Ll.ltrB efficiently targets DNA of a conserved relaxase domain in pcfG for insertion by a retro-transposition mechanism (Staddon et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The Ll.LtrB group II intron from the low G+C grampositive bacterium Lactococcus lactis interrupts a putative relaxase gene (ltrB), which is present on three conjugative elements: the pRS01 (48.4 kb) (Mills et al 1996) and pAH90 (26.5 kb) (O'Sullivan et al 2001) plasmids, and an integrative and conjugative element called the sex factor (50 kb) (Shearman et al 1996). L. lactis is a mesophilic lactic acid bacterium (LAB) that is widely used in the dairy industry, for instance, in the manufacturing of cheese.…”
Section: Introductionmentioning
confidence: 99%
“…Ll.LtrB was the first bacterial group II intron that was shown to splice (Mills et al 1996;Shearman et al 1996) and invade new sites in vivo (Mills et al 1997). The detailed retrohoming and retrotransposition pathways of Ll.LtrB were studied in L. lactis and Escherichia coli (Cousineau et al 1998(Cousineau et al , 2000Ichiyanagi et al 2002Ichiyanagi et al , 2003Coros et al 2005;Smith et al 2005).…”
Section: Introductionmentioning
confidence: 99%